Implementation of Islamic Values in Forming the Social Character of Elementary School Students - Rahim, Abdul; Karim; Nur Zahra, Wa Ode (TAKSONOMI: Jurnal Penelitian Pendidikan Dasar, 2024)
Islamic education does not only focus on teaching religious teachings, but also on developing positive social character. This study aims to examine the role of Islamic education in shaping the social character of students in the school. The method used is a qualitative approach with data collection techniques through in-depth interviews with students, teachers, and parents, as well as observations of learning and extracurricular activities. The results of the study showed that students who were actively involved in religious-based extracurricular activities, such as religious studies and social services, showed better social character development. In addition, family support in religious and social education at home also contributed significantly to the formation of students' social character. In conclusion, Islamic education has a major influence on the formation of students' social character, but the involvement of all parties in the school, family, and community is needed to optimize the results of social character education. This study provides an important picture of the integration of religious and social education in the formation of better character in students